Automated inspection using database technology within the aerospace industry - Tiwari, Ashutosh; Vergidis, Kostas; Lloyd, R.; Cushen, J. (Sage, 2008)
Many manufacturing processes have become fully automated resulting in high production volumes. However, this is not the case for inspection. Shortening the inspection times in manufacturing industry using the available information resources can result in the reduction of production lead-time and overall costs. Rapid advances in machine tool technology have resulted in fast processing computer numerical control (CNC) machines that are capable of manufacturing parts at high speeds, turning their manual inspection process into a bottleneck. However, most CNC machines record the operations that they perform as realization logs. This paper proposes an approach that utilizes these realization logs for automating the inspection process. The automation occurs with the implementation of a software tool that imports and compares the realization logs with the manufacturing instructions for a manufactured part. The output of the tool is an inspection report that lists all the identified skipped or mishandled operations for that part. The proposed inspection approach is compared with the manual practice within an aerospace manufacturer. The results demonstrate drastic reduction in production lead-time while producing accurate and reliable inspection reports in an automated manner.
Keywords: inspection process; database technology; wing assembly; wing manufacturing